Genomic instability related to zinc deficiency and excess in an in vitro model: is the upper estimate of the physiological requirements recommended for children safe? - Padula, Gisel (2017)
Micronutrients are important for the prevention of degenerative diseases due to their role in maintaining genomic stability. Therefore, there is international concern about the need to redefine the optimal mineral and vitamin requirements to prevent DNA damage. We analyzed the cytostatic, cytotoxic, and genotoxic effect of in vitro zinc supplementation to determine the effects of zinc deficiency and excess and whether the upper estimate of the physiological requirement recommended for children is safe. To achieve zinc deficiency, DMEM/Ham’s F12 medium (HF12) was chelated (HF12Q). Lymphocytes were isolated from healthy female donors (age range, 5–10 yr) and cultured for 7 d as follows: negative control (HF12, 60 μg/dl ZnSO4); deficient (HF12Q, 12 μg/dl ZnSO4); lower level (HF12Q + 80 μg/dl ZnSO4); average level (HF12Q + 180 μg/dl ZnSO4); upper limit (HF12Q + 280 μg/dl ZnSO4); and excess (HF12Q + 380 μg/dl ZnSO4). The comet (quantitative analysis) and cytokinesis-block micronucleus cytome assays were used. Differences were evaluated with Kruskal-Wallis and ANOVA (p < 0.05). Olive tail moment, tail length, micronuclei frequency, and apoptotic and necrotic percentages were significantly higher in the deficient, upper limit, and excess cultures compared with the negative control, lower, and average limit ones. In vitro zinc supplementation at the lower and average limit (80 and 180 μg/dl ZnSO4) of the physiological requirement recommended for children proved to be the most beneficial in avoiding genomic instability, whereas the deficient, upper limit, and excess (12, 280, and 380 μg/dl) cultures increased DNA and chromosomal damage and apoptotic and necrotic frequencies.